On the one-phase reduction of the Stefan problem with a variable phase change temperature. (February 2015) - Myers, T.G.; Font, F.
Abstract: The one-phase reduction of the Stefan problem, where the phase change temperature is a variable, is analysed. It is shown that problems encountered in previous analyses may be traced back to an incorrectly formulated Stefan condition. Energy conserving reductions for Cartesian, cylindrically and spherically symmetric problems are presented and compared with solutions to the two-phase problem.